Late Pleistocene pollen assemblages from Gokarna Formation (Dhapasi section) in Kathmandu valley, Nepal - Paudayal, Khum N (Journal of Nepal Geological Society, 2007)
Pollen assemblages of the Gokarna Formation were studied from a 27 m thick section near Dhapasi, Kathmandu. The analysis of 42 sediment samples revealed six zones. The lower part of the sequence was deposited under temperate climatic conditions. The dominance of Pinus, Abies, and Picea with a very low percentage of Quercus and Castanopsis indicates a temperate climate during the deposition of the lower part of the sequence. The dominance of Castanopsis and Quercus along with other angiosperms (Betula, Myrica, Ulmus, and Oleaceae) over gymnosperms (Pinus, Abies, and Picea) indicates subtropical to warm climatic conditions in the middle part of the sequence. A change to a cool temperate climate took place towards the top of the sequence with the increase of Pinus, Picea and Abies, and decrease of Quercus and other woody angiosperms. The subtropical element Castanopsis decreases and ultimately disappears at the top of the sequence. An increase of herbaceous plants and Poaceae also supports the advent of a colder climate, which ultimately prevailed during the deposition of the Thimi Formation. A characteristic feature of the Gokarna Formation is the dominance of woody angiosperms over gymnosperms except in the lower part of the section. Journal of Nepal Geological Society, 2006, Vol. 33 pp.33-38